SOCS2 regulates T helper type 2 differentiation and the generation of type 2 allergic responses. - FALLON, PADRAIC; AMU, SYLVIE; SAUNDERS, SEAN; NEL, HENDRIK (My University, 2011)
The incidence of allergy and asthma in developed countries is on the increase and this trend looks likely to continue. CD4+ T helper 2 (Th2) cells are major drivers of these diseases and their commitment is controlled by cytokines such as interleukin 4, which are in turn regulated by the suppressor of cytokine signaling (SOCS) proteins. We report that SOCS2?/? CD4+ T cells show markedly enhanced Th2 differentiation. SOCS2?/? mice, as well as RAG-1?/? mice transferred with SOCS2?/? CD4+ T cells, exhibit elevated type 2 responses after helminth antigen challenge. Moreover, in in vivo models of atopic dermatitis and allergen-induced airway inflammation, SOCS2?/? mice show significantly elevated IgE, eosinophilia, type 2 responses, and inflammatory pathology relative to wild-type mice. Finally, after T cell activation, markedly enhanced STAT6 and STAT5 phosphorylation is observed in SOCS2?/? T cells, whereas STAT3 phosphorylation is blunted. Thus, we provide the first evidence that SOCS2 plays an important role in regulating Th2 cell expansion and development of the type 2 allergic responses.
PUBLISHED
PMID: 21646394
Keywords: Respiratory disease; Allergy; atopic dermatitis; hyperresponsiveness; lung resistance; schistosome soluble egg antigen; suppressor of cytokine signaling; Immunology, Inflammation & Infection